Mining Management Gold Without a License in Kuantan District Singingi - Saiyed, Rahma (Decision, 2023)
In order to effectively address illicit gold mining in Kuantan Singingi Regency, the community and the government must work together. The application of this strategy using a collaborative visioning and network management approach is covered in this article. The primary focus is on how stakeholder analysis, coordinating tactics, and interactions help achieve shared objectives when combating illicit activity. The Kuantan Singingi Regency authorities acted decisively in response to the expansion of illegal gold mining in the region. All relevant stakeholders are involved in the execution of policies, which builds an efficient implementation network. Through in-depth study and thoughtful consideration of the practical actions done by local governments, this essay seeks to investigate these elements. The purpose of this essay is to provide readers a better understanding of how network management and cooperative visioning operate together to implement laws intended to stop illegal gold mining. This article is anticipated to offer theoretical and practical guidance and contributions in the field of public policy by outlining the stages, goals, and outcomes of implementation. This study employs a qualitative methodology to describe the three primary phases of Kuantan Singingi Regency policy implementation.